Laser printing method of stainless steel powder, three-dimensional component and heat treatment method of three-dimensional component
By combining S-03 stainless steel powder with specific chemical composition and infrared laser scanning parameters with staged heat treatment, the traditional forming problem of S-03 stainless steel has been solved, enabling the manufacture of high-density and high-efficiency three-dimensional components suitable for complex structures and high-performance applications.
Patent Information
- Application Number
- CN202511151224.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-15
- Publication Date
- 2025-11-07
- Estimated Expiration
- 2045-08-15
AI Technical Summary
Traditional forging or casting processes for S-03 stainless steel make it difficult to form thin-walled curved surfaces and internal cavity structures, resulting in inherent limitations in the processing of complex three-dimensional components, and casting is prone to internal defects.
Using S-03 stainless steel powder with a specific chemical composition ratio, combined with a large-layer thick powder layer and multiple sets of infrared laser scanning parameters, high-density forming is achieved through laser printing. Residual stress is reduced through staged heat treatment, and forming efficiency and performance are optimized.
It has achieved high density (≥99.991%) and high efficiency in the manufacturing of three-dimensional components, broadened the application range of complex structures, reduced internal defects and internal stress, and improved manufacturing freedom and performance consistency.
Smart Images

Figure CN120901298A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of additive manufacturing, in particular to a laser printing method of stainless steel powder, a three-dimensional component and a heat treatment method thereof. BACKGROUND
[0002] The conventional S-03 stainless steel (grade 022Cr12Ni10MoTi) is manufactured by forging or casting process. The forging process is constrained by the mold and cannot form thin-walled curved surfaces and internal cavity structures. The casting process is prone to internal defects due to insufficient melt flow, thereby leading to inherent limitations in forming complex three-dimensional components and difficulty in achieving fine structure processing. SUMMARY
[0003] In view of this, the present application provides a laser printing method of stainless steel powder to realize efficient and dense forming of S-03 stainless steel powder under the condition of a larger powder layer thickness, taking into account printing efficiency and component density.
[0004] In addition, it is necessary to provide a three-dimensional component and a heat treatment method thereof.
[0005] A laser printing method of stainless steel powder, comprising the steps of: laying a layer of stainless steel powder with a thickness of 0.05-0.07mm on a substrate or a previous layer of solidified layer in a forming cavity, the material of the stainless steel powder layer includes, by mass fraction: carbon ≤0.03%, silicon ≤0.15%, manganese ≤0.15%, phosphorus ≤0.008%, sulfur ≤0.006%, chromium 11.5%-12.5%, nickel 9.0%-10.3%, molybdenum 0.5%-0.8%, titanium 0.15%-0.25%, aluminum ≤0.2%, and the balance of iron; under the protection of inert gas atmosphere, according to the preset three-dimensional model slice data, controlling the infrared laser beam to selectively scan the stainless steel powder layer according to the predetermined scanning strategy, so that the scanned and irradiated stainless steel powder layer melts and solidifies to form a cladding layer; repeating the above steps to print layer by layer until the three-dimensional component is completed, wherein the scanning strategy includes any one group of parameters selected from the following: (1) infrared laser power 200-250W, scanning pitch 0.08-0.11mm, scanning speed 700-900mm / s; (2) infrared laser power 250-300W, scanning pitch 0.08-0.11mm, scanning speed 900-1100mm / s; (3) infrared laser power 300-400W, scanning pitch 0.07-0.09mm, scanning speed 800-1000mm / s.
[0006] In some possible embodiments, the predetermined scanning strategy further includes: implementing S-shaped reciprocating filling scanning in the internal region of the two-dimensional section corresponding to the three-dimensional model slice data.
[0007] In some possible implementation manners, the predetermined scanning strategy further comprises: rotating the filling scanning direction of each layer by 67 degrees relative to the previous layer, and performing a contour scanning on the two-dimensional section after completing the filling scanning on the internal region.
[0008] In some possible implementation manners, the parameter package is: the scanning pitch is 0.09 mm, the laser power is 250 W, the scanning speed is 900 mm / S, and the energy density is 51.44 J / mm 3 .
[0009] In some possible implementation manners, the parameter package is: the scanning pitch is 0.09 mm, the laser power is 350 W, the scanning speed is 900 mm / S, and the energy density is 72.02 J / mm 3 .
[0010] In some possible implementation manners, the parameter package is: the scanning pitch is 0.1 mm, the laser power is 300 W, the scanning speed is 1050 mm / S, and the energy density is 47.62 J / mm 3 .
[0011] In some possible implementation manners, the thickness of the stainless steel powder layer is 0.06 mm.
[0012] In some possible implementation manners, the inert gas is argon or nitrogen, and the wavelength of the infrared laser beam is 1064 nm.
[0013] A stainless steel three-dimensional component prepared by the above laser printing method, wherein the density of the three-dimensional component is not less than 99.991%.
[0014] A heat treatment method of the three-dimensional component, comprising the steps of: heating the three-dimensional component to 600-900 DEG C, holding for 1-5 hours, and air quenching; heating the three-dimensional component to 600-900 DEG C, holding for 1-5 hours, and air quenching; heating the three-dimensional component to 400-700 DEG C, holding for 2-5 hours, and air cooling.
[0015] The present application realizes the significant improvement of forming efficiency while maintaining the high density of ≥99.991% by selecting the S-03 stainless steel powder with specific chemical composition ratio and particle size range (1553 μm), combining the optimized large layer thickness powder laying (0.05-0.07 mm) and multiple sets of infrared laser scanning parameter packages in an inert atmosphere; wherein different parameter packages can meet the forming requirements of low internal stress, high efficiency and high density, effectively solving the technical problems of S-03 stainless steel in the background art, such as low absorption rate in the infrared band leading to difficulty in large layer thickness printing, low efficiency of traditional SLM process and easy occurrence of internal defects, and endowing the component with higher manufacturing freedom and performance consistency, widening its application range in complex structure and high performance application fields. BRIEF DESCRIPTION OF DRAWINGS
[0016] Figure 1 The flow chart of the laser printing method of the stainless steel powder provided by an embodiment of the present application.
[0017] Figure 2 The flow chart of the heat treatment method of the stainless steel three-dimensional component provided by an embodiment of the present application. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present application will be described clearly and completely in combination with the drawings in the embodiments of the present application. Obviously, the described embodiments are only some of the embodiments of the present application, not all the embodiments.
[0019] It should be noted that when an element is considered to be "connected" to another element, it can be directly connected to the other element or can exist in a middle element at the same time. When an element is considered to be "arranged on" another element, it can be directly arranged on the other element or can exist in a middle element at the same time.
[0020] In the present application, the laser printing device includes a laser generator, an optical system, a forming cavity, a powder laying device, an inert gas protection system and a control system. The working principle of the laser printing device is that the control system controls the laser generator to generate a laser beam with a specific power and wavelength according to the preset three-dimensional model slicing data, and after focusing by the optical system, the laser beam selectively scans and melts the laid metal powder layer in the inert gas protected forming cavity, so that the powder is melted and solidified to form a three-dimensional solid component layer by layer.
[0021] In the present application, the heat treatment equipment includes a heat treatment furnace, a temperature control system, a protective atmosphere system and a cooling system. The working principle of the heat treatment equipment is to accurately control the temperature in the heat treatment furnace through the temperature control system, and to uniformly heat treat the printed three-dimensional component according to the predetermined process conditions (such as temperature and holding time); the protective atmosphere system can ensure the stability of the furnace environment and prevent oxidation; the cooling system gradually reduces the component temperature according to the preset cooling mode, such as furnace cooling or air cooling, to obtain the target organizational performance.
[0022] See Figure 1 An embodiment of the present application provides a laser printing method of stainless steel powder, which is used for realizing efficient manufacturing of a stainless steel three-dimensional component, and the stainless steel three-dimensional component has the advantages of low internal stress and high density. The laser printing method comprises the following steps: S1: A layer of stainless steel powder layer with a thickness of 0.05-0.07 mm is laid on the substrate or the previous solidified layer in the forming cavity. Preferably, the thickness of the stainless steel powder layer is 0.06 mm.
[0023] In the present embodiment, the material of the stainless steel powder layer in step S1 comprises the following components in mass fraction: carbon ≤0.03%, silicon ≤0.15%, manganese ≤0.15%, phosphorus ≤0.008%, sulfur ≤0.006%, chromium 11.5%-12.5%, nickel 9.0%-10.3%, molybdenum 0.5%-0.8%, titanium 0.15%-0.25%, aluminum ≤0.2%, and the balance of iron. The grade of the stainless steel powder is 022Cr12Ni10MoTi, and the stainless steel powder is prepared by a gas atomization method, the powder is regular spherical, and the particle size range of the powder is 15-53 μm.
[0024] S2: Under the protection of an inert gas atmosphere, according to the preset three-dimensional model slicing data, an infrared laser beam is controlled to selectively scan the stainless steel powder layer according to a predetermined scanning strategy, so that the scanned and irradiated stainless steel powder layer is melted and solidified to form a cladding layer. The scanning strategy includes any one group of parameters selected from the following: (1) Infrared laser power 200-250 W, scanning pitch 0.08-0.11 mm, and scanning speed 700-900 mm / s; in the printing process with the parameter package (1), the energy input of the laser is relatively lower, and the printing density can be maintained, which is suitable for printing the stainless steel three-dimensional component with high deformation control requirement of the stainless steel three-dimensional component. The low energy input introduces less heat accumulation and heat cycle, which can reduce the internal stress of the stainless steel three-dimensional component, thereby reducing the deformation risk of the internal stress of the stainless steel three-dimensional component. Preferably, the scanning pitch is 0.09 mm, the laser power is 250 W, the scanning speed is 900 mm / s, and the energy density is 51.44 J / mm 3 .
[0025] (2) Infrared laser power 250-300W, scanning pitch 0.08-0.11mm, scanning speed 900-1100mm / s; in the printing process with parameter package (2), the laser power is high, the scanning pitch is large, and the scanning speed is high, the energy input per unit time is high, which is suitable for manufacturing stainless steel three-dimensional components with simple shape and stable structure, and ensures high manufacturing efficiency per unit time. Preferably, the scanning pitch is 0.09mm, the laser power is 350W, the scanning speed is 900mm / s, and the energy density is 72.02J / mm 3 .
[0026] (3) Infrared laser power 300-400W, scanning pitch 0.07-0.09mm, scanning speed 800-1000mm / s. After printing with parameter package (3), the printed stainless steel three-dimensional components have the highest density and fewest defects. Preferably, the scanning pitch is 0.1mm, the laser power is 300W, the scanning speed is 1050mm / s, and the energy density is 47.62J / mm 3 .
[0027] Wherein, the infrared laser power P refers to the energy size of the infrared waveband laser beam output by the laser generator per unit time, the unit is watt (W), which is used to represent the heating capacity of the laser on the stainless steel powder layer; the scanning pitch h refers to the distance between adjacent two scanning paths, the unit is (mm). The scanning speed refers to the moving speed of the laser beam on the powder layer surface. The energy density refers to the energy size input by the laser in unit volume of powder material, and its calculation formula is: In the formula, Ev is the volume energy density (J / mm3), P is the laser power (W), v is the scanning speed (mm / s), h is the scanning pitch (mm), and t is the single-layer powder laying thickness (mm). The energy density is used to comprehensively evaluate the influence of laser power, scanning speed, scanning pitch and layer thickness on the melting degree of the powder.
[0028] In the embodiment, the predetermined scanning strategy of step S2 includes: implementing S-shaped reciprocating filling scanning in the internal region of the two-dimensional section corresponding to the three-dimensional model slice data, and the S-shaped reciprocating filling refers to that when the laser beam continuously scans in a single direction in the internal filling region of each layer, the path thereof presents a continuous “S” shape or Zigzag shape (Zigzag) turning motion. Specifically, after the laser beam scans along a parallel line to the end point of the line segment, the laser is not turned off and the laser head is not lifted, but directly scans the next parallel line in the opposite direction of the previous line segment at the adjacent scanning pitch, and the directions are alternated in this way until the filling of the internal region of the layer is completed.
[0029] The predetermined scanning strategy of step S2 further comprises: rotating the filling scanning direction of each layer by 67° relative to the previous layer to reduce residual stress; after completing the internal area filling scanning, performing scanning on the two-dimensional cross-sectional profile again to improve the surface accuracy and density of the component.
[0030] S3: fully melting and solidifying the stainless steel powder in the scanned area to form a cladding layer.
[0031] In the embodiment, the stainless steel powder melted by the laser beam is rapidly solidified into a uniform and dense cladding layer in step S3, and the process is carried out under inert gas protection to inhibit oxidation and splashing pollution, thereby ensuring that the internal structure of the formed stainless steel three-dimensional component is uniform and delicate, and high density is obtained.
[0032] S4: repeating steps S1 to S3 to print layer by layer until the stainless steel three-dimensional component is completed. The density of the stainless steel three-dimensional component is not less than 99.991%. The density refers to the volume proportion of the component inside excluding voids, and high density means higher component strength, better electrical conductivity and thermal conductivity.
[0033] Compared with the prior art, the laser printing method of the stainless steel powder provided by the present application has the following advantages: (1) The present application selects S-03 stainless steel powder with a specific chemical composition ratio, and combines with optimized large layer thickness powder laying (0.05-0.07mm), S-type reciprocating filling scanning and 67° interlayer rotation scanning strategy, so that the large layer thickness powder can be fully melted and uniformly solidified under infrared laser irradiation, thereby significantly improving the single-layer printing thickness and printing efficiency while ensuring the forming accuracy, and breaking through the problem of low efficiency caused by the limited layer thickness (usually less than 20μm) in the prior art.
[0034] (2) The present application establishes an energy density parameter system composed of laser power, scanning speed, scanning spacing and layer thickness, and selects three best parameter packages with low stress, high efficiency and high density in multiple parameter tests, so that the density of the prepared component can reach more than 99.991% and the porosity is less than 0.004%, thereby significantly improving the forming difficulty of S-03 stainless steel with low absorption rate in the infrared band and easy to produce internal defects, and realizing the comprehensive optimization of strength, plasticity and manufacturing efficiency.
[0035] Please refer to Figure 2 , the present application further provides a heat treatment method of a stainless steel three-dimensional component, comprising the following steps: S5: placing the stainless steel three-dimensional component in step S4 in a heat treatment device, setting the heat treatment temperature to 600-900℃, the holding time to 1-5 hours, and air quenching to room temperature.
[0036] S6: The stainless steel three-dimensional component in step S5 is heated again to 600-900°C, the holding time is 1-5 hours, and air quenching is performed to room temperature.
[0037] S7: The stainless steel three-dimensional component in step S6 is heated again to 400-700°C, the holding time is 2-5 hours, and air cooling is performed to room temperature. This achieves high electrical conductivity, thermal conductivity, and moderate mechanical properties, as shown in Table 1.
[0038] Table 1: Mechanical property results of the stainless steel three-dimensional component The present application effectively reduces the residual stress of the stainless steel three-dimensional component, improves the uniformity of the microstructure, and improves the elongation and impact toughness of the stainless steel three-dimensional component by designing a staged heat treatment process, i.e., performing two 600-900°C air quenching and one 400-700°C air cooling.
[0039] The present application is described in detail below in conjunction with representative embodiments to help understand the spirit of the present application, but does not limit the scope of the present application in any way.
[0040] Laser printing: First, prepare the stainless steel powder (S-03 stainless steel powder, brand: 022Cr12Ni10MoTi), and set the printing layer thickness of the laser printing equipment to 60 μm. The substrate in the forming cavity is preheated to 100°C. Then, different parameter packages of laser power (250-350 W), scanning speed (600-900 mm / s), and scanning interval (0.07-0.10 mm) are used for selective laser melting (SLM) printing of the powder to obtain multiple stainless steel three-dimensional component samples. Next, the samples prepared by printing are subjected to metallographic polishing and polishing treatment, the microstructure is observed, and the porosity is measured to evaluate the density of the samples, and the best parameter package is selected. See Table 2 for different parameter packages and porosities.
[0041] Table 2. Laser printing parameter packages and porosities In Table 2, the porosity refers to the percentage of the volume of internal voids in the component to the total volume of the component within the range of microstructure observation, which is used to evaluate the density of the component; the maximum defect size refers to the characteristic size of the largest single hole or inclusion in the component measured under microscopic observation, in units of microns (μm), which directly reflects the severity of the internal defects of the component.
[0042] It can be seen that for parameter package (1): infrared laser power 200-250 W, scanning pitch 0.08-0.11 mm, scanning speed 700-900 mm / s; for example, the No. 2 sample (power 250 W, pitch 0.09 mm, scanning speed 900 mm / s, energy density 51.44 J / mm³) obtains an ultra-low porosity of 0.006% and a smaller maximum defect size of 28.0 μm while maintaining a lower energy input, balancing high density and low residual stress forming effect.
[0043] For parameter package (2): infrared laser power 250-300 W, scanning pitch 0.08-0.11 mm, scanning speed 900-1100 mm / s; for example, the No. 19 sample (power 300 W, pitch 0.1 mm, scanning speed 1050 mm / s, energy density 47.62 J / mm³) still maintains a low porosity of 0.009% and a maximum defect size of 29.6 μm under the condition of larger scanning pitch and higher scanning speed, achieving a balance between high forming efficiency and good density; For parameter package (3): infrared laser power 300-400 W, scanning pitch 0.07-0.09 mm, scanning speed 800-1000 mm / s; for example, the No. 10 sample (power 350 W, pitch 0.09 mm, scanning speed 900 mm / s, energy density 72.02 J / mm³) achieves the lowest porosity of only 0.003% and the smallest defect size of 17.3 μm under high power conditions, with the highest density and the best forming quality.
[0044] Heat treatment: the stainless steel three-dimensional components processed by parameter package (1), parameter package (2) and parameter package (3) are placed in a heat treatment device according to the following heating and cooling scheme: first, the stainless steel three-dimensional components are placed in the heat treatment device, the heat treatment temperature is set to 600-900 ℃, the holding time is 1-5 hours, and the gas quenching is cooled to room temperature. Then, the stainless steel three-dimensional components are heated to 600-900 ℃ again, the holding time is 1-5 hours, and the gas quenching is cooled to room temperature. Finally, the stainless steel three-dimensional components in step S6 are heated to 400-700 ℃ again, the holding time is 2-5 hours, and the air cooling is cooled to room temperature, completing the heat treatment.
[0045] Room temperature tensile test: after the above heat treatment, the stainless steel three-dimensional components obtained by parameter package (1)-(3) are detected for tensile and room temperature impact performance at room temperature according to GB / T228.1-2021 (metal material tensile test Part 1: room temperature test method), the results are shown in Table 3: Table 3: room temperature tensile test results of examples Wherein, the sample direction Z refers to the tensile direction of the sample being parallel to the building direction (the forming layer stacking direction) of the component in the laser printing process, i.e. perpendicular to the direction of each layer powder laying plane; the sample direction XY refers to the tensile direction of the sample being parallel to the single layer powder laying plane of the component in the laser printing process, i.e. stretching test is carried out along the horizontal direction.
[0046] It can be seen from Table 3 that under the printing condition of parameter package (1), the Z-direction tensile strength of the stainless steel three-dimensional component can reach 984 MPa, and the elongation is 18%, and the XY-direction tensile strength can reach 1001 MPa, and the elongation is 20%, so that the plasticity performance is good while the high strength is maintained, which shows that the parameter package effectively reduces the residual stress of the component under the condition of low energy input, and is suitable for low internal stress printing with high requirement for forming deformation control; Under the printing condition of parameter package (2), the Z-direction tensile strength of the stainless steel three-dimensional component is 959-968 MPa, and the elongation is 14.5%-15%, and the XY-direction tensile strength can reach 1008-1012 MPa, and the elongation is 14.5%-16.5%, so that higher printing efficiency per unit time is realized under the premise of ensuring the strength, which is suitable for high-efficiency printing of large quantities of simple shape and stable structure; Under the printing condition of parameter package (3), the Z-direction tensile strength of the stainless steel three-dimensional component is 943-954 MPa, and the elongation is 14%-15%, and the XY-direction tensile strength can reach 992-1024 MPa, and the elongation is 15.5%-16.5%, so that the porosity and the minimum defect size are extremely low, which is suitable for high-density printing with extremely high requirement for structural density.
[0047] Room temperature impact test: the stainless steel three-dimensional components obtained by printing according to parameter packages (1)-(3) are detected for impact performance at room temperature (U-shaped notch) according to GB / T229-2020 (metal materials-Charpy pendulum impact test method), and the results are shown in Table 4: Table 4: results of room temperature impact test (U-shaped notch) of examples According to the requirement of standard GB / T229-2020, the impact energy is greater than or equal to 108 KU2 (J), so it can be seen that the stainless steel three-dimensional components obtained according to parameter packages (1)-(3) after the above heat treatment are all significantly higher than the standard requirement, wherein the impact energy of parameter package (1) is 176.0-187.0 KU2 (J), which shows excellent toughness and impact resistance; the impact energy of parameter package (2) is 132.5-133.0 KU2 (J), which still has good toughness while maintaining the advantage of high-efficiency printing; the impact energy of parameter package (3) is 159.0-172.0 KU2 (J), which balances the strength and toughness while ensuring high density, which reflects the balanced optimization effect of the heat treatment system of the present application between strength and toughness.
[0048] Comparative Example 1, the stainless steel three-dimensional component is heat treated according to GJB 7960-2012 (Specification for hot-rolled (forged) stainless steel bars for rockets), which includes the following steps: first solution treatment: 750℃±10℃ for 1h, air cooling or water quenching, then aging treatment: 500℃±10℃ for 2h, air cooling. Then tensile test at room temperature according to GB / T 228.1-2021, the results are shown in Table 5.
[0049] Table 5: Room temperature tensile test results of Comparative Example 1 It can be seen that the traditional solution + aging heat treatment process adopted in Comparative Example 1 can make the tensile strength of the Z-direction sample reach 1052-1041 MPa, and the elongation rate is 12.0%-12.5%, but the elongation rate of the XY-direction sample is only 9.5%-10.5%, and the lowest reduction of area is only 54.5%, which is significantly lower than the standard requirements of ≥11% elongation rate and ≥60% reduction of area.
[0050] This shows that due to the large difference in microstructure characteristics and internal stress distribution between the samples manufactured by SLM technology and forged or cast components, the use of traditional solution + aging heat treatment specification alone will lead to significant anisotropy of the samples along the XY and Z directions, especially the transverse (XY) plasticity decreases significantly, even lower than the standard requirements, which is difficult to meet the application requirements of high toughness components. In contrast, the staged heat treatment system proposed in the present application can significantly improve the elongation rate in each direction while maintaining the strength, reduce anisotropy, and obtain better comprehensive mechanical properties.
[0051] In summary, the present application can realize high-efficiency preparation of S-03 alloy parts with large layer thickness (0.05-0.07mm) by infrared laser equipment, with high manufacturing freedom, especially suitable for complex structure and prototype manufacturing. According to the high-efficiency parameter calculation, the maximum manufacturing efficiency of a single laser can reach 22.68cm³ / h, and with the HBD-P400 four-laser equipment, the theoretical maximum manufacturing efficiency can reach 90.72cm³ / h, significantly improving the production capacity.
[0052] In addition, the staged heat treatment system provided by the present application can obtain higher elongation rate and toughness without significantly reducing the strength compared with the traditional solution + aging heat treatment scheme, effectively improving the anisotropy problem of SLM formed components. In contrast, if the SLM printed sample is treated according to the traditional standard heat treatment scheme, the elongation rate will often be low or even lower than the standard requirements, which is difficult to meet the application requirements of high-performance components. The method of the present application not only optimizes the printing efficiency and density, but also considers the balance and stability of mechanical properties.
[0053] In addition, those skilled in the art will recognize that the application described herein can be embodied as a system, method or computer program in instructions, code or code segments. The application described herein can be implemented using software and / or hardware including a computer or Processing unit. Accordingly, changes in software and / or firmware and / or hardware can be made without departing from the scope of the application. It is therefore contemplated to cover any and
Claims
1. A laser printing method of a stainless steel powder, characterized by, The method comprises the steps of: Laying a stainless steel powder layer with a thickness of 0.05-0.07 mm on a substrate or a previous solidified layer in a forming cavity, the stainless steel powder layer comprising, in terms of mass fraction, carbon ≤0.03%, silicon ≤0.15%, manganese ≤0.15%, phosphorus ≤0.008%, sulfur ≤0.006%, chromium 11.5%-12.5%, nickel 9.0%-10.3%, molybdenum 0.5%-0.8%, titanium 0.15%-0.25%, aluminum ≤0.2%, and the balance of iron; Under an inert gas protection atmosphere, controlling an infrared laser beam to selectively scan the stainless steel powder layer according to preset three-dimensional model slicing data and a predetermined scanning strategy, so that the scanned and irradiated stainless steel powder layer is melted and solidified to form a cladding layer; Repeating the above steps to print layer by layer until a three-dimensional component is completed, wherein the scanning strategy comprises any one parameter package selected from the following: (1) infrared laser power 200-250 W, scanning pitch 0.08-0.11 mm, and scanning speed 700-900 mm / s; (2) infrared laser power 250-300 W, scanning pitch 0.08-0.11 mm, and scanning speed 900-1100 mm / s; (3) infrared laser power 300-400 W, scanning pitch 0.07-0.09 mm, and scanning speed 800-1000 mm / s.
2. The laser printing method of claim 1, wherein, The predetermined scanning strategy further comprises: implementing S-shaped reciprocating filling scanning in an internal region of a two-dimensional cross section corresponding to the three-dimensional model slicing data.
3. The laser printing method of claim 2, wherein, The predetermined scanning strategy further comprises: rotating the filling scanning direction of each layer by 67° relative to a previous layer, and performing contour scanning of the two-dimensional cross section after completing the filling scanning of the internal region.
4. The laser printing method of claim 1, wherein, The parameter package is: the scanning interval is 0.09mm, the laser power is 250W, the scanning speed is 900mm / S, and the corresponding energy density Ev is 51.44J / mm 3 .
5. The laser printing method of claim 1, wherein, The parameter package is: the scanning interval is 0.09mm, the laser power is 350W, the scanning speed is 900mm / S, and the corresponding energy density Ev is 72.02J / mm 3 .
6. The laser printing method of claim 1, wherein, The parameter package is: the scanning interval is 0.1mm, the laser power is 300W, the scanning speed is 1050mm / S, and the corresponding energy density Ev is 47.62J / mm 3 .
7. The laser printing method of claim 1, wherein, The thickness of the stainless steel powder layer is 0.06 mm.
8. The laser printing method of claim 1, wherein, The inert gas is argon or nitrogen, and the wavelength of the infrared laser beam is 1064 nm.
9. A stainless steel three-dimensional member produced by the laser printing method according to any one of claims 1 to 8, characterized by The three-dimensional component has a density of not less than 99.991%.
10. A method of heat treating a three-dimensional structure as claimed in claim 9, characterized in that The method comprises the steps of: Heating the three-dimensional component to 600-900 ℃, maintaining for 1-5 hours, and air quenching; Heating the three-dimensional component to 600-900 ℃, maintaining for 1-5 hours, and air quenching; Heating the three-dimensional component to 400-700 ℃, maintaining for 2-5 hours, and air cooling.
Citation Information
Patent Citations
Selective laser melting method used for mold steel powder
CN111761062A
Martensitic stainless steel surface laser cladding remanufacturing method
CN116732513A
Preparation process of selective laser melting forming high-elongation 316L stainless steel
CN118268590A
Duplex stainless steel powder for laser additive manufacturing as well as preparation method and application of duplex stainless steel powder
CN119615020A